Forensic Medicine in Indonesia: The Application of Visum ET Repertum in Case Resolution - Yogi Prasetyo1 , Ferry Irawan Febriansyah2 , Indiantoro3 , Absori4 , Chrisna Bagus Edhita Praja5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This research aimed at explaining important comprehension concerning with Forensic medicine inIndonesia: the application of visum et repertum in case resolution. As we know that, the community stillhave not known and comprehended about how important visum et repertum in law is. Moreover, it is oftenoccurred uncompleted law well as the impact of not being supported by visum et repertum. This researchutilized normative research method, which studied about medicine forensic and visum et repertum. Mainmaterial that was used in this research was data in form of health laws and regulations and also other datawhich were contained in books, journals and various scientific works and they related to the research theme.Furthermore, visum et repertum is one of important elements that cannot be abandoned in medical forensicprocess.